Maximizing Data Transmission Rate for Implantable Devices Over a Single Inductive Link: Methodological Review - Trigui, Aref; Hached, Sami; Ammari, Ahmed Chiheb; Savaria, Yvon; Sawan, Mohamad (IEEE reviews in biomedical engineering, 2019)
Due to the constantly growing geriatric population and the projected increase of the prevalence of chronic diseases that are refractory to drugs, implantable medical devices (IMDs) such as neurostimulators, endoscopic capsules, artificial retinal prostheses, and brain-machine interfaces are being developed. According to many business forecast firms, the IMD market is expected to grow and they are subject to much research aiming to overcome the numerous challenges of their development. One of these challenges consists of designing a wireless power and data transmission system that has high power efficiency, high data rates, low power consumption, and high robustness against noise. This is in addition to minimal design and implementation complexity. This manuscript concerns a comprehensive survey of the latest techniques used to power up and communicate between an external base station and an IMD. Patient safety considerations related to biological, physical, electromagnetic, and electromagnetic interference concerns for wireless IMDs are also explored. The simultaneous powering and data communication techniques using a single inductive link for both power transfer and bidirectional data communication, including the various data modulation/demodulation techniques, are also reviewed. This review will hopefully contribute to the persistent efforts to implement compact reliable IMDs while lowering their cost and upsurging their benefits.